Evolution of policy for the treatment of substance use disorders in Qatar - Majid Alabdulla; Nimesh Samarasinghe; Iain Tulley; Shuja Reagu (BMC, 2022)
Abstract There is a marked paucity of published evidence on the extent and nature of substance use disorders in the State of Qatar. This is mirrored by a dearth of information on the policy for the treatment of substance use disorders in the public domain. Between 2007 and 2017, substance use disorders have risen from the third to leading cause of disability in Qatar. More recently, Qatar has shifted from applying a punitive only paradigm in managing substance use problems to recognizing the role of treatment and care for people with substance use disorders. Recently published official documents in Qatar define addiction as a disease and as a chronic condition where people with substance use disorders should be treated as patients who need care and assistance. This shifts the onus of providing, and developing services, for individuals with substance use disorders with healthcare providers rather than purely with the criminal justice system. Following cabinet approval, the recently established Permanent Committee for Addiction Treatment headed by the Minister of Public Health, signals the need to institutionalize systems and structures to upscale demand reduction programmes in the country. This article is a descriptive examination of the shifts in substance abuse treatment policy in Qatar, the major factors influencing this evolution, and will utilise some of the policy science theories to describe and analyse policy outcomes. The article will also frame the substance use problem in Qatar for the first time, based on documents published by various government organisations.